Analisis Kesalahan Konjugasi Modal Verben dalam Kalimat Sederhana Bahasa Jerman - Nahas, Maksimus; Rijal, Syamsu; Azizah, Laelah (Academic : Journal of Social and Educational Studies, 2025)
Abstract. The aim of this research is to describe students' errors in conjugating modal verbs and the factors that lead to these errors. This research is a descriptive qualitative study. The population of this research consists of 152 students of class XII science. The sample of this research is 32 students of class XII Science 6 of SMAN 12 MAKASSAR who were randomly selected (random sampling) to determine the class, subject of study represents. Data collection was done through tests and questionnaires. Based on the data analyses, a total of 352 conjugation errors were found in the modal verbs. There were 75 errors for can (47%), 50 errors for must (31%), 56 errors for like (35%), 65 errors for may (41%), 60 errors for want (37%) and 44 errors for should (27%). The total number of conjugation errors of modal verbs in simple sentences in German by the students of Class XII Science 6 of SMAN 12 Makassar is 37% and falls in the “high” category. The factors that lead to these errors are lack of understanding of the concepts of modal verbs in German, especially in the area of grammar, vocabulary as well as influence of mother tongue. There are differences in the grammatical structure between the German language and the native languageKeywords: : Error analysis, Modal Verben , German